Histopathology of placenta in intrauterine growth restriction (IUGR) - Khajuria, Ruchi; Sharma, Megha (International Journal of Research in Medical Sciences, 2019)
Background: Birth of healthy term baby depends on normal placenta. IUGR is a condition associated with placental insufficiency. There is a close relationship between IUGR and placental qualitative changes. The aim of the present study was to evaluate the morphological and histological changes in placentas of IUGR fetuses and in placentas of normal uncomplicated pregnancies and to determine the relationship that exists between morphological change and frequency of IUGR. Methods: In a cross sectional study conducted in the department of Pathology, GMC Jammu, a total of 60 placenta were received, 30 placenta of IUGR fetus (group 1-case) and 30 placenta of uncomplicated pregnancy with normal single fetus (group 2-control). Exclusion criteria: Twin pregnancy, gestational hypertension, diabetes, congenital anomaly, antepartum hemorrhage and systemic disorder. Results: Placental weights in IUGR group were significantly lower than control group. Average placental weight in IUGR group was 425 gms while in the control group (normal placenta) it was 550 gms. Infarction, intervillous thrombosis, chorionic villitis, hemorrhagic endovasculitis, placental intravascular thrombi, perivillous fibrin deposition, fibrinoid necrosis and villous edema were found to be more common in IUGR group (Group 1-case group) than Normal (Group 2- control group). Conclusions: This study highlightened that significant pathological differences were found between the placentas of IUGR fetus and normal fetus. The gross and microscopic measurement of a placenta is a good way to get proper information about IUGR and helps in management of the pregnancy.